Association between Insertion/Deletion Polymorphism in Angiotension Converting Enzyme and Susceptibility to Schizophrenia - Hajar Mazaheri; Mostafa Saadat (Tehran University of Medical Sciences, 2015)
Background: The activity of angiotension converting enzyme (ACE; OMIM: 106180) in different brain regions of patients with schizophrenia changed, suggesting a possible involvement of ACE in psychiatric disorders. Genetic polymorphism of insertion/deletion (I/D; dbSNP rs4646994) in the gene encoding ACE has been well defined. Methods: The present case-control study was performed on 363 (268 males, 95 females) in-patients with schizophrenia diagnosis, and 363 (268 males, 95 females) healthy blood donor controls. The genotypes of I/D ACE polymorphism were determined using PCR method. PCR products were separated and sized by electrophoresis on a 2% agarose gel. The insertion allele (I) was detected as a 478 bp band, and the deletion allele (D) was visualized as a 191 bp band. The association between genotypes of the I/D polymorphism and the schizophrenia risk was examined by use of odds ratios (OR) and 95% of confidence intervals (CIs). Results: Among females, the II genotype significantly decreased the risk of schizophrenia compared with the DD genotype (OR=0.18, 95%CI: 0.04-0.72, P=0.015). There was significant linear trend for the number of the I allele and schizophrenia risk among females (Chi2=5.19, P=0.023). There was no significant association between I/D polymorphism and susceptibility to schizophrenia among male subjects. There was significant interaction between gender and the II genotype (P=0.031). Conclusion: The II genotype of the I/D polymorphism has a protective effect for schizophrenia among females.